LAPORAN KEUANGAN MASJID SEBAGAI WUJUD TANGGUNG JAWAB HUKUM ATAS AMANAH AL-QUR’AN DAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN 45 (PSAK 45) (Studi Deskriptif Pada Masjid K.H. Ahmad Dahlan Universitas Muhammadiyah Kupang) - MUHAMMAD SADAM; Fitriningsih Amalo; Suryaningsi (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2022)
This study aims to determine the application of mosque financial statements referring to the values ​​of the Qur'an about trust, referring to the values ​​of the Qur'an about responsibility and based on the statement of financial accounting standards 45 (PSAK 45) at Masjid KH. Ahmad Dahlan, University of Muhammadiyah Kupang. This research is a descriptive qualitative research. The types and sources of data in this study are primary and secondary data. Data collection techniques in this study were interviews, observation and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation, verification. The results of this study are the takmir has carried out the mandate in the presentation of financial statements, has carried out responsibilities in financial reports and shows that the financial statements of the KH mosque. Ahmad Dahlan, University of Muhammadiyah Kupang still presents financial reports in a simple form, in the form of cash income and expenditure reports, this shows that the KH mosque. Ahmad Dahlan, University of Muhammadiyah Kupang, the financial statements presented are not in accordance with the statement of financial accounting standards 45 (PSAK 45).